Indicators of the Internationalization of the Social Sciences and Humanities - Heilbron, Johan; Boncourt, Thibaud; Sapiro, Gisèle; Sorá, Gustavo; Karady, Victor; Brisson, Thomas; Jeanpierre, Laurent; Lee, Kil-Ho (Serendipities. Journal for the Sociology and History of the Social Sciences, 2017)
This contribution, which is part of the collaborative European research project INTERCOSSH, presents indicators for studying the internationalization of the social and human sciences. Five dimensions are distinguished and for each one of them various indicators are presented. Although neither the dimensions nor the indicators are exhaustive, they capture some of the most significant aspects of internationalization. They pertain to international scholarly associations, international scholarly journals, the flows and meanings of book translations, transnational authorship, and policies of internationalization. In addition to these dimensions, three particular areas of inquiry are presented: changing relations between the North and the South, between Western and Eastern Europe, and between the West and Asia.